Elastic behavior of polymer melts : rheology and processing - Münstedt, Helmut, 1941- (Hanser Publishers, Hanser Publications, 2019)
"Understanding the elastic properties of polymer melts is necessary for ensuring successful polymer processing and thus producing high-quality plastic parts. This unique book is the first to focus on this important topic. Starting with the molecular origin of elastic behavior and an explanation of the physical quantities involved, experimental methods and the dependence of elastic behavior on experimental parameters are then presented. Elastic properties of filled and unfilled systems are compared directly, and polymer blends are also considered. Elastic effects in various applications are included, such as in extrudate swell, internal stresses, and shrink films, to illustrate the importance of this field in the plastics processing industry"--
Keywords: polymerní taveniny; pružnost; reologie; polymer melts; elasticity; rheology; monografie; monographs